1995
DOI: 10.1016/0009-2614(95)00488-p
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon resonance enhanced MPI-PES above the lowest ionization threshold. Observation of the [a1Δ]5pπ 2Φ state of the SH (SD) radical

Abstract: Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University of Amsterdam, Secretariat, Singel 425, 1012 WP Amsterdam, The Netherlands. You will be contacted as soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The combination of REMPI and TOF-MS is a well-known tool for the selective detection of trace compounds in complex matrixes. The main advantages of this technique are the selective ionization of minor components in a complex matrix, the great sensitivity and resolution, major ionization efficiency, and the possibility of simultaneous analysis of different components present in a matrix. Those advantages made the REMPI-TOF-MS technique one of the most promising analytical methods as reflected by the increasing research carried out recently in this field. …”
mentioning
confidence: 99%
“…The combination of REMPI and TOF-MS is a well-known tool for the selective detection of trace compounds in complex matrixes. The main advantages of this technique are the selective ionization of minor components in a complex matrix, the great sensitivity and resolution, major ionization efficiency, and the possibility of simultaneous analysis of different components present in a matrix. Those advantages made the REMPI-TOF-MS technique one of the most promising analytical methods as reflected by the increasing research carried out recently in this field. …”
mentioning
confidence: 99%
“…While all them have in common the laser desorption step they differ in their ionisation method. Within this category the laser multiphoton ionisation coupled with time-of-flight mass spectrometry, and in particular resonance-enhanced multiphoton ionisation (REMPI)-time-of-flight mass spectrometry (TOFMS) can be considered as one of the most powerful methods for the analysis of trace components in complex matrix [8][9][10][11][12][13][14][15][16][17].The high selectivity of REMPI-TOFMS is given by the combination of the mass selective detection with the resonant ionisation process: the ionisation is produced by the successive absorption of two or more laser photons. Thus for an efficient ionisation, the energy of the first photon has to be resonant with one of the real electronic states in the molecule (resonance enhancement).…”
mentioning
confidence: 99%
“…In the vacuum ultraviolet (VUV) region, several Rydberg states of SH have been observed. 32–35 Morrow obtained the one-photon VUV absorption spectrum of SH/SD between 123 and 200 nm, 32 and seven Rydberg states were identified: B 2 Σ − [(2π) 2 4s] (which is the first doublet Rydberg state, labeled as 2 2 Σ − in later literature), 2,3 C 2 Σ − [(2π) 2 4P σ ], 2,3,33 E 2 Σ − [(2π) 2 3D σ ] 2 , and D, F, G, and H 2 Δ [(2π) 2 n d σ , n = 3–6] 2 states that converge to the X 3 Σ − ground ionic state of SH. Later on, 2+1 resonance enhanced multiphoton ionization (REMPI) studies observed another Rydberg state with the X 3 Σ − ionic core, 2 Π [(2π) 2 4P π ], 33 and fourteen more Rydberg states that converge upon the excited ionic states a 1 Δ and b 1 Σ + of SH + .…”
Section: Introductionmentioning
confidence: 99%
“…Later on, 2+1 resonance enhanced multiphoton ionization (REMPI) studies observed another Rydberg state with the X 3 Σ − ionic core, 2 Π [(2π) 2 4P π ], 33 and fourteen more Rydberg states that converge upon the excited ionic states a 1 Δ and b 1 Σ + of SH + . 34,35 In general, these Rydberg states are bound in the Franck-Condon (FC) region of SH and are correlated with higher excited states of the S atom product. The experimental and theoretical investigations on the photodissociation of SH/SD via the higher repulsive electronic states remain limited.…”
Section: Introductionmentioning
confidence: 99%